The Paleolithic archaeology of Shirak Province and the open-air site of Aghvorik - Glauberman, Phil (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
Shirak Province in the Republic of Armenia is very rich in Paleolithic sites. Since the first discovery of Paleolithic artifacts in the 1930s, chance finds and field investigations by numerous scholars and archaeological expeditions have brought to light several new localities and findspots, among which the open-air site complex at Aghvorik is currently the most prominent. The Paleolithic sites of Shirak are geomorphologically associated with the Ashotsk Plateau in the north, the Shirak Depression and northwestern slopes of Mt. Aragats in the south, and the Akhuryan River gorge in the west. These areas contain several sources of high-quality lithic raw materials, including dacite, obsidian, and flint. The geomorphic and topographic locations of Paleolithic sites relate to phases of Plio-Pleistocene volcanism, glaciations in high elevation uplands, and the lacustrine and alluvial dynamics that formed the paleorelief and paleoenvironment. Lithic artifact assemblages generally present techno-typological characteristics consistent with early and late phases of the Acheulian, as observed at Lower Paleolithic sites in the Armenian Highlands and Southern Caucasus. While currently fewer in number than Lower Paleolithic finds, Middle Paleolithic artifacts obtained from sites in Shirak tend to be better preserved and made mainly of obsidian, while some dacite artifacts have also been documented. Shirak is also rich in paleontological, or zooarchaeological sites that have yielded a range of Pleistocene macro- and micro-faunal remains. While the Paleolithic archaeological, biostratigraphic, and geological records of Shirak have not yet been subject to systematic documentation and synthesis, the area holds great potential for future research to enlarge and complement the database of Pleistocene human occupation and environment in the broader region.